Analysis of Factors that Influence the Use of Electronic Money in Indonesia - Puspa Nada Aliyah Akbar (International Journal of Science and Society, 2023)
Electronic money would be a new type of money for everyone to use for day-to-day spending. This research empirically examines the factors affecting Indonesian citizens to use electronic money. These factors are financial literacy, security of electronic money, ease of useful, and role of goverment. The research method used is quantitave research and descriptive and verificative approach. The sample of the research comprised 210 potential electronic money users in Indonesia. The research result indicate that finansial literacy, security of electronic money, ease of useful, and role of government is significantly affect the use of electronic money.